Towards the concordant integration of airport expansion into urbanization. Using the Berlin Brandenburg airport region as a case study. - Yang, Yang (My University, 2015)
Based on case studies of European gateway airports, this thesis is introducing linear regression models to investigate the correlations between airport capacity and its impacts on demographics (population density, aging population ratio and unemployment ratio), and the tendency of land use changes in the neighboring regions. At last, significant regression resultants are used to predict the demographic and land use changes in the Berlin Brandenburg (BER) international airport region, and an implementation example is given. GIS (Geographic Information System) applications allow users to analyze spatial information in an intuitive way. ArcGIS hot spot analysis and density analysis are introduced for investigating common grounds in land use distribution, using case studies of other European airport regions, e.g. the industrial and commercial cluster of an airport's ground traffic corridors; airport impact range on diverse land usage; airport noise impact on the adjoining residential development; etc. The investigation of strategies for re-establishing urban image and urban branding is an important part of the present work. In the knowledge-based economy era urban image and urban branding play an important role in urban revitalization, especially in a new airport region. In the case of the BER airport region, a "mental city" outlined by the local authority is even more important than the existing conditions of the "physical city". A proper urban image accompanied by efficient planning and design strategies may not only retain the confidence, reputation and the sense of belonging of local residents, but also highly promote competitiveness at both regional and community level. Therefore, investigation on a proper urban image for an airport region, as well as strategies for establishing such image, is also an important component of this thesis.
Keywords: Verkehr; Flughafen; Standort; Stadtregion; Wirtschaftssektor; Wirkung; Regionalwirtschaft; Raumentwicklung; Stadtplanung; Bevölkerungsentwicklung; Dichte; Flächennutzung; Industrie; Gewerbe; Geographisches Informationssystem; Cluster; Stadtmarketing; Städtevergleich